A multimedia data visualization based on Ad Hoc communication networks and its application to disaster management - Kawamura, Y.; Wagner, M.; Jang, Hyong Doo; Nobuhara, H.; Shibuya, T.; Kitahara, I.; Dewan, A.; Veenendaal, B. (2015)
After massive earthquakes and other large-scale disasters, existing communication infrastructure may become unavailable and, therefore, it can be quite difficult for relief organizations to fully grasp the impact of the disaster on the affected region. Consequently, this will be the cause of delays to offer the strategic assistance, and to provide water and food, etc. In order to solve the problem of re-establishing communication infrastructure to allow for information gathering, we developed an ad hoc mobile communications network for disaster-struck areas using ZigBee. As the communication speed of ZigBee is low, we propose a problem-specific image compression method for the multimedia data visualization. By using the proposed method combined with GPS information, it is possible to quickly grasp the damage situation in the region. Through our communication experiments in Tsukuba City, Japan we confirm the effectiveness of our system as a disaster information gathering and management system.